Microglial activation and hypothalamic structural plasticity in HFD obesity: insights from semaglutide and minocycline - Xi Rong; Fang Wei; Yuqi Jiang; Qintao Ma; Dongmei Wang; Jie Shen (Journal of Lipid Research)
High-fat diet (HFD)-induced microglial activation contributes to hypothalamic inflammation and obesity, but the mechanisms linking microglia to structural changes remain unclear. This study explored the role of microglia in impairing hypothalamic synaptic plasticity in diet-induced obesity mice and evaluated the therapeutic potential of semaglutide (Sema) and minocycline (MI). Six-week-old C57BL/6J mice were divided into low-fat diet and HFD groups. At week 30, the HFD-fed mice were treated daily with Sema or MI for six weeks. Confocal microscopy assessed hypothalamic dendritic spines, synaptic organization, and microglia–synapse interactions. We also analyzed microglial morphology, CD68/CD11b colocalization with Iba-1, synaptic marker expression, and phagocytosis-related pathways (C1q, C3, CD11b). BV2 microglia were used to examine the direct effects of Sema or MI on microglia and validate the in vivo findings. HFD feeding induced microglial activation, as indicated by increased colocalization of CD68 or synaptophysin and CD11b with Iba-1, along with elevated C1q, C3, and CD11b expression, signaling enhanced synaptic phagocytosis. This was accompanied by reduced hypothalamic dendritic spines, decreased synaptic marker expression, and disrupted excitatory/inhibitory synaptic organization in the melanocortin system, as well as impaired glucose metabolism, disrupted leptin-ghrelin balance, and increased food intake and body weight. Sema and MI treatments reversed the pathological changes of microglial activation and restored hypothalamic synaptic structure, although their effects on synaptic organization and metabolic outcomes differed. Our findings highlight the key role of microglial activation in hypothalamic synaptic impairment in diet-induced obesity models, with Sema and MI possibly offering distinct therapeutic pathways to mitigate these impairments.